Barriers for implementation of successful change to prevent musculoskeletal disorders and how to systematically address them. (November 2018) - Yazdani, Amin; Wells, Richard
Abstract: This scoping review identified common barriers and facilitators encountered during the implementation of changes to prevent musculoskeletal disorders (MSD) and examined their relationship with those encountered in general Occupational Health and Safety (OHS) efforts. Thematic analysis of the literature identified 11 barriers: (i) Lack of time; (ii) Lack of resources; (iii) Lack of communication; (iv) Lack of management support, commitment, and participation; (v) Lack of knowledge and training; (vi) Resistance to change; (vii) Changing work environment; (viii) Scope of activities; (ix) Lack of trust, fear of job loss, or loss of authority; (x) Process deficiencies; and (xi) Difficulty of implementing controls. Three facilitators identified were: (i) Training, knowledge and ergonomists' support; (ii) Communication, participation and support; and (iii) An effective implementation process. The barriers and facilitators identified were similar to those in general OHS processes. The integration of MSD prevention into a general management system approach may overcome these barriers. Highlights: 11 themes identified as barriers and 3 as facilitators of MSD prevention. A management system approach can systematically address barriers to MSD prevention. Management commitment and worker participation are essential for MSD prevention. Comprehensive training should be implemented alongside ergonomic interventions. Interventions must be culturally relevant and easy to integrate into work duties.